Intravenous lidocaine as adjuvant to general anesthesia in renal surgery. Issue 1 (1st January 2018) - Nakhli, Mohamed Said; Kahloul, Mohamed; Guizani, Taieb; Zedini, Chekib; Chaouch, Ajmi; Naija, Walid
ABSTRACT: The role of intraoperative intravenous lidocaine infusion has been previously evaluated for pain relief, inflammatory response, and post-operative recovery, particularly in abdominal surgery. The present study is a randomized double-blinded trial in which we evaluated whether IV lidocaine infusion reduces isoflurane requirement, intraoperative remifentanil consumption and time to post-operative recovery in non-laparoscopic renal surgery. Sixty patients scheduled to undergo elective non-laparoscopic renal surgery under general anesthesia were enrolled to receive either systemic lidocaine infusion (group L: bolus 1.5 mg/kg followed by a continuous infusion at the rate of 2 mg/kg/hr until skin closure) or normal saline (0.9% NaCl solution) (Group C). The depth of anesthesia was monitored using the Bispectral Index Scale (BIS), which is based on measurement of the patient's cerebral electrical activity. Primary outcome of the study was End-tidal of isoflurane concentration (Et-Iso) at BIS values of 40–60. Secondary outcomes include remifentanil consumption during the operation and time to extubation. Et-Iso was significantly lower in group L than in group C (0.63% ± 0.10% vs 0.92% ± 0.11%, p < 10 –3) . Mean remifentanil consumption of was significantly lower in group L than in group C (0.13 ± 0.04 µg/kg/min vs 0.18 ± 0.04 µg/kg/min, p < 10 –3 ). Thus, IV lidocaine infusion permits a reduction of 31% in isoflurane concentration requirement and 27% in the intraoperative remifentanil need. In addition, recovery from anesthesia and extubation time was shorter in group L (5.8 ± 1.8 min vs 7.9 ± 2.0 min, p < 10 –3 ). By reducing significantly isoflurane and remifentanil requirements during renal surgery, intravenous lidocaine could provide effective strategy to limit volatile agent and intraoperative opioids consumption especially in low and middle income countries.